Generalization of FuzzyContra- Continuous Functions in Fuzzy Topological Space - Salim dawood Mohisn (Al-Qadisiyah Journal of Pure Science, 2017)
in this paper, we devoted the generalization of some types of fuzzy contra-continuousfunctionsnamely fuzzy contra-g-continuous with study and discussion some properties of thesetypes, also we shows relationships between these types.Keywords:- ((fuzzy g-closed set, fuzzy contra-g- continuous function, fuzzy21 T -space, fuzzy gcompactspace, fuzzy continuous function))